Analisis Wacana Kritis Teks Pemberitaan â€œPenolakan Timnas Israel pada Piala Dunia U-20 Indonesiaâ€ di Kompas.com dan Minanews.net - Asrorur Rahim; Nurhayati Nurhayati (Balai Bahasa Provinsi Riau, 2024)
This study aims to understand the ideology of news texts in the online media Kompas.com and Minanews.net in reporting on the polemic against the Israeli national team's rejection of the U-20 World Cup in Indonesia which sparked debate and disagreements. Many groups have pros and cons against Israel in competing in the U20 World Cup which was held in Indonesia. This research method uses descriptive qualitative analysis and this article uses the Fairclough three-dimensional framework approach as an analytical tool and selects news about the rejection of the Israeli national team based on two different news media on Kompas.com and Minanews.net. After analysis, it was found that Kompas.com tended to support and did not make a problem of Israel competing in the U20 World Cup competition and found no objections directed at the Israeli national team, while Minanews.net tended to support rejecting the Israeli national team so that they would not be given the right to compete in the U20 World Cup in Indonesia.